2017
DOI: 10.1002/jcb.26400
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Effects of cyclin D1 gene silencing on cell proliferation, cell cycle, and apoptosis of hepatocellular carcinoma cells

Abstract: This study aims to investigate the effects of Cyclin D1 silencing on cell cycle, cell proliferation, and apoptosis of hepatocellular carcinoma cells (HCC). Cells were divided into the blank group, negative control group (HCC cells transfected with control shRNA), Cyclin D1 shRNA group (HCC cells transfected with Cyclin D1 shRNA), and the normal group (human normal liver L-02 cells). Expressions of Cyclin D1, Caspase-3, Bcl-2, and C-myc were detected by RT-qPCR and Western blotting. Cell proliferation was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…Cyclin-D1, a regulator of cell cycle at the G 1 to S transition, was also overexpressed in HCC tissues. High expression of cyclin-D1 was also correlated with tumor stage in HCC (19). Silencing of C-FLIP, XIAP, cyclin-D1, or MCL-1 by small interfering ribonucleic acid (siRNA) or short hairpin RNA inhibited cell proliferation and triggered apoptosis in HCC cell lines (4,6,20).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin-D1, a regulator of cell cycle at the G 1 to S transition, was also overexpressed in HCC tissues. High expression of cyclin-D1 was also correlated with tumor stage in HCC (19). Silencing of C-FLIP, XIAP, cyclin-D1, or MCL-1 by small interfering ribonucleic acid (siRNA) or short hairpin RNA inhibited cell proliferation and triggered apoptosis in HCC cell lines (4,6,20).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1, belonging to the highly conserved cyclin family, forms an active complex with CDK4 or CDK6 to drive cell cycle transition from G1 to the S phase . Overexpression of cyclin D1 or hyperactivation of CDK4 directly result in dysregulation of cell cycle and cell proliferation .…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1, belonging to the highly conserved cyclin family, forms an active complex with CDK4 or CDK6 to drive cell cycle transition from G1 to the S phase. 22,23 Overexpression of cyclin D1 or hyperactivation of CDK4 directly result in dysregulation of cell cycle and cell proliferation. 23,24 Our data show that CABYR-a/b knockdown leads to an increased ratio of cells in G0/G1 phase, suppression of cell proliferation, and downregulation of cyclin D1 and CDK4, suggesting that CABYR-a/b downregulation affects HCC cell proliferation by regulating cyclin D1 and CDK4 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Kunter et al confirmed that inhibition of PI3K/Akt signaling could arrest HCC cells at the G 0 /G 1 phase by regulating Rb/E2F1 (40). Chen et al indicated that silencing of cyclin D1 could arrest HCC cells in the G 0 /G 1 phase (41). In addition, CDK4 was found to be enzymatically activated by D-type cyclins to inactivate retinoblastoma, and thus arrest G1/S transition (42).…”
Section: Discussionmentioning
confidence: 99%